PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI ALFABET DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN KELAS I SD NEGERI 70 BANDA ACEH - Khairuman Rasmi; Teuku Mahmud; Raziska Ibrahimi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is a continuous process aimed at shaping the quality of human beings who continue to develop as preparation for the future. Basic education plays an important role as an initial foundation in building students’ academic abilities, especially early reading skills in lower-grade elementary school students. Early reading is a fundamental skill that must be mastered by first-grade students as a basis for subsequent learning. This study aims to determine the effect of using alphabet animated video learning media on improving early reading skills of first-grade elementary school students. This study employed a quantitative approach with an experimental method using a One Group Pre-test Post-test design. The research subjects consisted of one group of students who were given a pre-test before the treatment and a post-test after the implementation of the alphabet animated video media. The data were analyzed using the Paired Sample t-Test. The results showed that the average pre-test score of students was 77.17, which increased to 90.86 in the post-test, with an increase of 13.69 points. The statistical test results showed a t-value of –4.473 with a significance value of 0.000 (p < 0.05), indicating that H₀ was rejected and H₁ was accepted. The conclusion of this study indicates that the use of alphabet animated video media has a significant effect on improving early reading skills of first-grade elementary school students and is also able to increase students’ motivation and activeness in the learning process. The suggestions are directed to teachers to utilize alphabet animated video media as an alternative learning medium for early reading instruction, schools are expected to support the provision of technology-based facilities, and future researchers are encouraged to develop similar studies with more varied subjects and learning media